2006
DOI: 10.1303/aez.2006.641
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of susceptibility under harsh environmental conditions in fenvalerate-resistant strains of the diamondback moth, Plutella xylostella (Lepidoptera: Yponomeutidae)

Abstract: Resistance to fenvalerate was examined in a laboratory-selected population of the diamondback moth, Plutella xylostella, during exposure through 10 generations. Selection results showed that LD 50 values rose from 0.003 mg per larva to 31.1 mg per larva and 36.7 mg per larva respectively, in replications 1 and 2 during those 10 generations. Resistant line moth eggs were significantly smaller than those of moths before selection. Therefore, we selected a subpopulation of resistant lines under harsh environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The decline in resistance in the field population indicates that if the insecticides implicated in resistance are removed from the spray schedule, reversion to susceptibility should be observable fairly rapidly in the field as was documented for D. citri previously (Coy, Liu, & Stelinski, ). Given the likelihood of fitness cost, it is possible that reduced insecticide use reduced the selection of resistant individuals and susceptibility among D. citri populations increased (Chen et al., ; Coy et al., ; Georghiou, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in resistance in the field population indicates that if the insecticides implicated in resistance are removed from the spray schedule, reversion to susceptibility should be observable fairly rapidly in the field as was documented for D. citri previously (Coy, Liu, & Stelinski, ). Given the likelihood of fitness cost, it is possible that reduced insecticide use reduced the selection of resistant individuals and susceptibility among D. citri populations increased (Chen et al., ; Coy et al., ; Georghiou, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, resistance to imidacloprid and thiamethoxam was unstable in field populations of D. citri in Florida in the absence of insecticide exposure under laboratory conditions. Unstable insecticide resistance has also been reported in the diamondback moth, Plutella xylostella (Linnaeus) (Chen, Sanada-Morimura, Yanagi, & Nakasuji, 2006); silverleaf whitefly, B. tabaci (Basit et al, 2011;Chen & Nakasuji, 2004); housefly, Musca domestica L (Keiding, 1953); red mite, Panonychus citri (McG.) (Inoue, 1979); and green peach aphid, Myzus persicae Sulz (Needham & Sawicki, 1971).…”
Section: For Example Increased Expression Of Bmgst2 In Bombyx Mori Andmentioning
confidence: 97%
“…For example, orange morphs of M. persica are less susceptible to insecticides than red and green morphs (Srigiriraju et al ., ). Second, increasing metabolic detoxification of toxicant target sites is a mechanism of resistance development (Brattsten et al ., ; Chen et al ., ). Esterases are frequently implicated in detoxification of organophosphates, carbamates, and pyrethroids by insects (Hemingway & Ranson, ; Srigriraju et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of defense-related detoxifying enzyme activity may provide information regarding the degree of tolerance that insect pest populations may exhibit to insecticides and may be useful tools for monitoring pest susceptibility to insecticides. It has been well established that detoxification enzymes play a substantial role in development of resistance; however, insect toxicity to insecticides can also evolve due to reduced penetration of toxicants, alterations of target sites, and behavioral modifications (Brattsten et al, 1986;Chen & Nakasuji, 2004;Chen et al, 2006). Bed bugs, Cimex lectularius L. (Hemiptera: Cimicidae), have reemerged as a major household pest within the USA.…”
Section: Introductionmentioning
confidence: 99%
“…When considering other parameters, a DBM line resistant to fenvalerate had significantly smaller eggs and a lower survival rate than the susceptible line (Chen et al, 2006a). The fenvalerate-resistant and susceptible lines were exposed to unfavourable dry and hot environments without selection pressure of fenvalerate in their subsequent study, and the resistant line showed higher mortality and its susceptibility to fenvalerate returned within 10 generations (Chen et al, 2006b). Similar to the present study, it also reveals that abiotic stressors could strongly direct the evolution of insecticide-resistant populations of insects.…”
Section: Effects Of Resistancementioning
confidence: 99%